An introduction to agricultural systems - Spedding, C. R. W. (Elsevier Applied Science, 1988)
This book has been written as an introduction to such a study and it concentrates on an overall view, rather than on the detail, partly because of the need to relate the latter to some larger picture in order to appreciate the relevance and significance of the detail. This problem-of seeing the relevance of component studies and the significance of physical, biological and economic detail, and indeed principles-is encountered by many agricultural students right at the beginning of their university careers.